Plan de mejoramiento para la empresa Delicate de Pereira dedicada a la producción y comercialización de prendas íntimas desechables (2014)
DELICATE, is an organization that is dedicated to the production and marketing of light intimate disposable, was born with the intention of supplementing a basic need in the market of the centers in Pereira, i.e. to bring these elements (disposable undies), since the new legislation forced relaxation centers to use this type of elements to operate. Despite the performance that has had up to now, the company as all organizations face administrative problems, commercial, financial and other, DELICATE is no stranger to this situation, because it was preliminarily determined that the company does not have a management software that allows you to take a systematic control, which respond timely to correct decision making and truthful information as required by the environment. In the area of marketing could establish that the company does not have a marketing strategy, have not determined its sales force, company has been limited to serve existing customers, causing a stagnation in sales, also performs the work of post sale, or know the satisfaction with which the customer receives the product so that it allows you to take corrective actions early in order to engender loyalty; There is a well-defined program of promotion and advertising, nor has strong commercial alliances, which allow the rotation of inventories, resulting in stagnation in them. This allowed to establish an improvement plan to address these shortcomings, as well as the plan of action, finally assesses the profitability of the organization with the proposed improvements.